Procesos de separación en contextos de violencia conyugal: Trayectorias desde la agencia - Villanueva Gutiérrez, Eva María (El Colegio de México A.C., 2015)
AbstractThis research note analyzes how the possibility of a break up within a violent conjugal realationship is built. This analysis is based on gathered information of ten narrative interviews made in Morelia City, Mexico to women that suffered conjugal violence, which are currently separated from their partners. In this reconstruction, emphasis is made on some of the factors that inhibited or promoted the separation. With this objective in mind, a relational approach about the dimensions of gender, resistances and social and material resources was developed. This research found that the possibility of separation is given by the configuration of a significant nucleus of resources; that means, in the accumulation and quality of the resources at their disposal and in the appropriation and framework of their subjectivities. This work underlies the interest of thinking about agency in abuse contexts